THE SHIFTING SEMANTICS OF “KAWAII”: HISTORICAL, CULTURAL, AND GENDERED TRANSFORMATIONS IN JAPANESE AESTHETIC PERCEPTION - Cynthia Lailanisa Soegiono; Nur Rosyidah (jfpublisher, 2025)
The Japanese concept of Kawaii often translated as “cute” or “adorable” has become an emblem of Japan’s global cultural identity. However, beyond its surface charm, Kawaii encapsulates a profound cultural discourse that intertwines emotion, gender, and power. This paper examines the shifting semantics and cultural functions of Kawaii from the Showa period to the Reiwa era, revealing how its meaning evolved from a symbol of fragile innocence to one of empowerment and diversity. Employing a qualitative and multimodal approach, the research draws from historical media artifacts such as Shoujo no Tomo (Girls’ Companion) magazine and contemporary visual representations alongside intergenerational interviews. The findings suggest that Kawaii functions as both a linguistic and ideological framework through which Japanese femininity, consumer identity, and self-expression are negotiated. Ultimately, Kawaii emerges as a dynamic aesthetic category that reflects broader sociocultural transformations, particularly the reconfiguration of gender and affect in modern Japan.